Comparison of Subjective Experiences and Effectiveness of First-Generation Long-Acting Injectable Antipsychotics and Risperidone Long-Acting Injectables in Patients With Schizophrenia. Issue 5 (October 2016) - Chen, Wen-Yin; Lin, Shih-Ku
Abstract : Abstract: We conducted a cross-sectional study to compare the subjective experiences and clinical effects of first-generation long-acting injectable (FGA-LAI) antipsychotics with those of risperidone long-acting injectables (RIS-LAIs) in 434 schizophrenia patients. Compared with the RIS-LAI group, the patients treated with FGA-LAIs had a significantly longer duration of illness and LAI treatment and were older. Our results suggest that patients treated with FGA-LAI have more satisfactory subjective experiences compared with patients treated with RIS-LAI and that both FGA-LAI and RIS-LAI treatments can prevent relapses and hospitalization. Additional longitudinal studies determining the long-term benefits of RIS-LAI are warranted. Abstract : Supplemental digital content is available in the text.